Family Functioning and Multiple Sclerosis: Study Protocol of a Multicentric Italian Project - Di Tella, Marialaura; Perutelli, Virginia; Miele, Giuseppina; Lavorgna, Luigi; Bonavita, Simona; De Mercanti, Stefania Federica; Streito, Lidia Mislin; Clerico, Marinella; Castelli, Lorys (Frontiers in Psychology, 2021)
Multiple Sclerosis (MS) is a chronic inflammatory and neurodegenerative disease, which not only affects physical functioning, but is also associated with cognitive impairments and great psychological distress. The combination of those symptoms may have negative consequences on the family functioning of patients with MS, with detrimental effects on both marital relationships and parental bonding. Furthermore, the presence of individual characteristics and of an adequate social support may also contribute to the quality and endurance of family relationships. Particularly, high levels of alexithymia, a personality trait that affects the recognition of a person’s own emotions, have been associated with reduced interpersonal communication skills and enhanced anxiety/depressive symptoms. Therefore, the main aim of the present study is to provide an in-depth evaluation of family functioning and related factors in patients with MS and their families. In order to reach this goal, the perceived quality of family functioning, dyadic relationships, and parental bonding will be first investigated. Secondly, the possible associations between the quality of family relationships and the presence of alexithymia, psychological distress, and perceived social support will be examined. Patients with MS and their families who will consent to take part in the study will be asked to provide sociodemographic and clinical information, and to complete a series of questionnaires, presented and uploaded on an online dedicated platform. The final sample will be made up of 300 families, consecutively recruited from the Italian medical centers involved in the project. The results of the present study will shed light on the family functioning of patients with MS, through a comprehensive assessment of the main factors that are associated with family dynamics. A holistic evaluation of those aspects can help clinicians and researchers understand family dynamics in MS population better.